Wooden architecture of Koli homes - Mumbai Archive Project Team (Jio Institute, 2024)
Timber, bamboo, thatch, and clay were the materials used to build Koli houses in the past. Concrete, cement, and ceramic tiles have mostly replaced these, although some old houses still feature wooden architecture.